Implikasi Yoga Marga Terhadap Kesehatan Rohani - Ni Made Yunitha Asri Diantary; I Made Hartaka (UHN IGB Sugriwa Denpasar, 2020)
Hindus have a noble purpose in life namely moksartham jagadhita ya ca iti dharma or attain jagadhita (physical well-being) and moksa (inner peace). This goal can be achieved by a variety of paths known as catur marga or catur yoga. Catur marga or catur yoga is a method or way that can be done to get closer between humans and God. The catur yoga marga are bhakti yoga, karma yoga, jnana yoga, and raja yoga. Each individual can take the path that he wants to pursue to reach God. This path is carried out with a sincere heart and in accordance with the conditions of each Hindu. Through this yoga path, Hindus can actualize their lives in accordance with their respective obligations. Self-control through mind control as a whole through the practice of meditation can be a medium in achieving this life goal. Control of the senses and the human mind is key in managing the mental and spiritual health of mankind. In yoga this self-control is very important and important to apply, so it is obligatory to do meditation in this life as a way to achieve spiritual health that is directly related to physical health. A healthy mind will mean creating a healthy body.